Challenges Faced by Caretakers of Intellectually Disabled Children - Riya, (THE PRIMARY TEACHER, 2022)
This study explores challenges faced by caregivers of intellectually disabled children. The study was conducted with a sample of 25 people (caretakers of intellectually disabled children) (N=25) both males and females from Fortis Hospital, New Delhi, and Global Institute of Medical Science, Bangalore, Udaan (NGO), New Delhi and Samarthanam (NGO) Bangalore. A five-point rating scale was used to collect data from caretakers with 5 domains: Social Stigma, Financial Concerns, Future Concerns, Happiness Quotient, and General Stress. The result of the study shows that there is a positive correlation between age and general stress level, between family income and general stress, and family income and happiness quotient. The study also reveals that there exists a mean rank difference in general stress among different occupations. It proved that the home employed population was having the least stress compared to other occupations, also there is a negative correlation between happiness quotient and social stigma